Socioeconomic Differences in Retirement Adjustment among the Elderly Residing in Retirement Homes (Croatian Sociological Review, 2019)
The ageing of the population in Croatia and an increase in the number of elderly persons who retain their retirement status for a longer period call for more research on retirement adaptation. This study was focussed on providing a clearer insight into the relationship between socioeconomic characteristics and retirement adjustment, as well as the identification of factors that could increase a low level of retirement adjustment in older people. The research was conducted as a survey in spring 2018 in retirement homes in the Croatian town of Bjelovar and the city of Zagreb. It included 211 older people of both genders aged 65 and above. Retirement Adjustment Factor Questionnaire was used to assess Atchley’s Model of Retirement Adjustment. The results confirmed the conceptual hypotheses from earlier studies. The socioeconomic characteristics of the participants such as level of education, type of retirement, monthly income level, and type of occupation were associated with the success of retirement adjustment in the Pre-Retirement, Honeymoon, Routine, and Termination phases from Atchley’s Model of Retirement Adjustment, while the Honeymoon Phase was related only to retirement length. Aside from promoting academic and public discussions on the topic, the study findings have potential implications for creating social programmes to improve the quality of life of the elderly and provide a better understanding of how the older population living in retirement homes experience retirement.